High-entropy energy materials: challenges and new opportunities. Issue 5 (13th April 2021) - Ma, Yanjiao; Ma, Yuan; Wang, Qingsong; Schweidler, Simon; Botros, Miriam; Fu, Tongtong; Hahn, Horst; Brezesinski, Torsten; Breitung, Ben
Abstract : An overview of high-entropy materials for energy applications, including H2 catalysis and storage, CO2 conversion, O2 catalysis and electrochemical energy storage, is given and the challenges and opportunities within this field are discussed. Abstract : The essential demand for functional materials enabling the realization of new energy technologies has triggered tremendous efforts in scientific and industrial research in recent years. Recently, high-entropy materials, with their unique structural characteristics, tailorable chemical composition and correspondingly tunable functional properties, have drawn increasing interest in the fields of environmental science and renewable energy technology. Herein, we provide a comprehensive review of this new class of materials in the energy field. We begin with discussions on the latest reports on the applications of high-entropy materials, including alloys, oxides and other entropy-stabilized compounds and composites, in various energy storage and conversion systems. In addition, we describe effective strategies for rationally designing high-entropy materials from computational techniques and experimental aspects. Based on this overview, we subsequently present the fundamental insights and give a summary of their potential advantages and remaining challenges, which will ideally provide researchers with some general guides and principles for the investigation and development of advanced high-entropy materials.